Patient preferences for receiving care, based on the age, gender, and/or attire of the dentist - Bonilla Cairo, Pablo Santiago (2023)
Objective: to determine the preferences of the patients in terms of age, sex and clothing of the dentists of two educational entities, public and private. Material and Methods: Basic descriptive cross-sectional study, for which the survey methodology was used by virtual means to a sample of 165 students from 8 to 25 years old divided into 3 groups, from 8 to 11 years, from 12 to 17 years and from 18 to 25 years of both sexes, photographs of 4 dental models were used: 2 women, one between 25 to 30 years old, another from 40 to 50 years old and two men of the same ages with 3 different uniforms, the processing of the data was through tables of frequencies and percentages. Results: The main outcome was the preference for a young female professional, wearing a pediatric dental jacket. Conclusions: It should be noted that the choice of the young professional was very marked in relation to the other three professionals; being 72.1% for the chosen one and the other professionals do not even reach 10% preference. It is also necessary to mention that the white apron that classically identifies the health professional was in second place of choice.